2007
DOI: 10.1097/01.mcg.0000225624.91791.fa
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Endoscopy After Myocardial Infarction Based on Cardiovascular Risk Categories

Abstract: Endoscopic procedures can be safely performed early post-MI without imparting a significant cardiopulmonary risk. Timing of endoscopy increases risk of complications, but evidence of significant recent cardiac damage as demonstrated by ST segment elevation, depressed left ventricular ejection fraction, or troponin-I peak greater than 1.6 ng/mL does not increase risk of cardiopulmonary complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…We suspect that this may be related to concerns from clinicians that the risks of the EGD may outweigh the benefit in these populations, in spite of the overall low complication rate of 0.5 % [2628]. Further, several studies have suggested that EGD performed for active bleeding within 30 days of myocardial infarction can be completed safely without significant added risk [29, 30]. Conversely, these groups of patients may be the least likely to tolerate an EVB due to their underlying cardiac and respiratory disease and consequently may derive more benefit from the prevention of an EVB then those with normal cardiac and lung function.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that this may be related to concerns from clinicians that the risks of the EGD may outweigh the benefit in these populations, in spite of the overall low complication rate of 0.5 % [2628]. Further, several studies have suggested that EGD performed for active bleeding within 30 days of myocardial infarction can be completed safely without significant added risk [29, 30]. Conversely, these groups of patients may be the least likely to tolerate an EVB due to their underlying cardiac and respiratory disease and consequently may derive more benefit from the prevention of an EVB then those with normal cardiac and lung function.…”
Section: Discussionmentioning
confidence: 99%
“…The important issue of elapsed time between the ACS and endoscopy with regard to incidence of complications was only assessed in one study. Indeed, Spier et al noted an inverse relationship between endoscopic complications from timing of ACS; in 135 patients, the only 2 complications occurred with endoscopy performed the same day as ACS, in contrast to no complications in procedures performed 24 hours or more after an ACS [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“… “x”: not reported. ENDO: data from two publications: Spier et al [ 8 ]and Sayana et al [ 15 ], in which several endoscopic modalities were used. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic ERCP has been shown to lead to less mortality and morbidity than surgery. Although upper gastrointestinal endoscopy and colonoscopy are relatively safe procedures after myocardial infarction (MI),48 ERCP is considered as a high-risk procedure after acute coronary syndrome (ACS) 9–11. ERCP has greater cardiovascular risks than any other endoscopic procedures because of longer procedure time, more anesthetic medications, frequent underlying cholangitis, and frequent need for therapeutic ERCP 12.…”
Section: Introductionmentioning
confidence: 99%